2019
DOI: 10.1039/c9ra07912b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new Pro-PYE ligands as co-catalysts toward Pd-catalyzed Heck–Mizoroki cross coupling reactions

Abstract: The present research work describes the synthesis of five new ligands containing pyridinium amine, [H 2 L 1 ] [OTf] 2 -[H 2 L 5 ][I] 2 from two new precursors, [P 3 Et ][I] and [P 2 Me ][CF 3 SO 3 ]. The structure elucidations of the compounds were confirmed by multinuclear NMR ( 1 H, 13 C), FT-IR and by single crystal XRD techniques. Theoretical DFT studies were carried out to get better insight into the electronic levels and structural features of all the molecules. These synthesized new Pro-PYE ligands [H 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…On the basis of surface area studies and electronic descriptor calculations, it is confirmed that both FBM and OBM have the ability to extract Pb from water and that OBM is more suitable for capturing Pb as compared to FBM. 53 Molecular descriptor data are given in Table S3.…”
Section: Solubility and Viscosities Of Polyimidesmentioning
confidence: 99%
“…On the basis of surface area studies and electronic descriptor calculations, it is confirmed that both FBM and OBM have the ability to extract Pb from water and that OBM is more suitable for capturing Pb as compared to FBM. 53 Molecular descriptor data are given in Table S3.…”
Section: Solubility and Viscosities Of Polyimidesmentioning
confidence: 99%
“…48 A series of in situ formed Pd catalysts with bis PYA ligands with the two PYA units bridged by cyclohexyl, pyridyl, and ethyl linkers display higher activity in the Mizoroki−Heck cross-coupling reaction under slightly milder conditions (up to 98% in 6 h; 130 °C, DMF, 0.01 mol % Pd). 86 While the exact bonding of the ligand to the palladium center is not known, the in situ formed catalyst succeeds in the olefination of a range of iodo-, bromo-, and even chlorobenzenes with >70% yield. Moreover, the rhodium(I) complex [RhCl(COD)( p-ph PYA)] (COD = cyclooctadiene) catalyzes the C−N bond crosscoupling between anilines and pyridinium amines to form secondary bis-aryl amines.…”
Section: ■ C−c Bond Formation Catalysismentioning
confidence: 99%
“…29 A few publications report the use of PYE ligands in catalysis. Douthwaite et al have shown that Pd(PYE) is analogous to Pd(NHC), and then Munir et al 30 reported Pd(PYE)-catalyzed Heck-Mizoroki cross coupling. Separation of charges allowed the modulate of catalytic activity in Ru complexes by changing the solvent polarity: both catalytic oxidation 31,32 and reduction 32 were dependent on polar cosolvent.…”
Section: Scheme 2 Previous Work On the Nqa Ligand's Donor Properties ...mentioning
confidence: 99%